Análise da redução da infiltração ao longo do tempo em um pavimento de blocos intertravados de concreto - Moreira, Lucas Sauer (2018)
Waterproofing is a problem that has been faced by big cities, especially in recent decades. The soil waterproofing causes that the water precipitated by the rain does not infiltrate as it happens in a natural terrain. It increases the superficial runoff and generates floods that bring serious economic damages and risks to public health. Considering that the conventional drainage system is not an adequate solution to face this problem, it has been invested in sustainable urban drainage. Among these sustainable measures are the land use laws and the use of permeable pavements, such as interlocking concrete blocks. In fact, some counties have already accepted this type of pavement as a permeable area in a terrain. However, the elaboration of permeable pavements rarely follows the norm or the specialized literature for its execution and no care is taken in relation to its maintenance, leading to improperly scaling in relation to the drainage characteristic. Therefore, this research aims to analyze the infiltration in these types of pavements most commonly executed over time. In order to do so, a new concrete interlocking block pavement was built and the analysis was made according to the different materials used in the settlement layer that was a mixture of medium sand with pea gravel, stone powder, and medium sand, in the course of 12 months through the tests of the Double Ring Infiltrometer and the American standard ASTM C1701. The two tests led to similar conclusions, showing a reduction of the infiltration capacity of the pavement over the course of 12 months. It was obtained that the permeability of the parts of the pavement constituted of the mixture of medium sand with pea gravel and only medium sand in the layer of settlement are considered medium, with infiltration rates after 12 months of 2,01.10-5 and 1.70.10-5 m/s, respectively, and the part with stone powder has permeability considered low, rendering ineffective the use of this material. It was also verified the influence of the granulometric distribution on the infiltration capacity of the pavement, not only the size of the grains being important, but also the uniformity of the grains to provide a suitable number of voids.